ANTIHYPERGLYCEMIC ACTIVITY OF IMPERATA CYLINDRICA ROOT METHANOL EXTRACT IN RATS - RUSLIN; ASPADIAH, VICA; DHIANAWATY, DIAH (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study aims to evaluate the inhibitory activity of Imperatacylindrica root methanol extract on glucose absorption level in intestine of male Wistar strain rats at a dose of 90 mg/kg-bw, which is a dose having antihypertensive activity. Methods: Extract inhibitory activity on the glucose absorption level in the intestine of the rats followed Soedigdo-Marsongkohadi method. Glucose absorption level was measured from a mixture of 30 mmol glucose in 0.9 % sodium chloride solution as the control solution and a mixture of the extract at the dose of 90 mg/kg-bw in another control solution as the tested solution Results: The result showed that the extract at the dose of 90 mg/kg-bw had significant activity (p<0.05) to decrease the glucose absorption level in the intestine of the rats. Conclusion: I. cylindrica root methanol extract at the dose of 90 mg/kg-bw had a significant activity to inhibit the glucose absorption level in the intestine of the rats. Thereby, the extract at the dose of 90 mg/kg-bw had antihyperglycemic activity.